TINJAUAN HUKUM ISLAM DAN HUKUM POSITIF TERHADAP PERKAWINAN BEDA AGAMA - Achmad Bilal Maulana; Muh. Jufri Ahmad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This writing aims to examine the similarities and differences between Islamic legal perspectives and positive legal perspectives on marriage problems of different religions or beliefs. The method used is qualitative, with a comparative approach. Literature study or literature study, which contains studies of relevant theories with interfaith marriage problems. This writing is normative formal juridical and also includes descriptive research, in studying Islamic principles, interfaith marriages are divided into three parts: marriage between Muslim men and girls who are not Muslim (Non-Muslim), marriage between Muslim men and women. Kitab, and the marriage of Muslim women to women. Men who are not Muslim (Non-Muslim). From a regulatory perspective, law enforcement is not strengthened in Indonesia, therefore Law Number 1 of 1974 concerning Marriage and Compilation of Islamic Law (KHI) is a constitutional law that prohibits other marriages. Therefore, the Office of Religious Affairs (KUA) and Marriage at the Civil Office (KCS) does not want to carry out different marriage administration data collection.